Plant breeding to control zinc deficiency in India: How cost-effective is biofortification? - Stein, Alexander J.; Nestel, Penelope; Meenakshi, J. V.; Qaim, Matin; Sachdev, H. P. S.; Bhutta, Zulfiqar A. (Cambridge University Press, 2007)
Objective: To estimate the potential impact of zinc biofortification of rice and wheat on public health in India and to evaluate its cost-effectiveness compared with alternative interventions and international standards. Design: The burden of zinc deficiency (ZnD) in India was expressed in disabilityadjusted life years (DALYs) lost. Current zinc intakes were derived from a nationally representative household food consumption survey (30-day recall) and attributed to household members based on adult equivalent weights. Using a dose–response function, projected increased zinc intakes from biofortified rice and wheat were translated into potential health improvements for pessimistic and optimistic scenarios. After estimating the costs of developing and disseminating the new varieties, the costeffectiveness of zinc biofortification was calculated for both scenarios and compared with alternative micronutrient interventions and international reference standards.